The Influence of Organizational Culture, Business Strategy for Increase in Performance Organizational Tourism - Indah Kusumawati; Agus Yulistiyono (Indonesian Journal of Society Development, 2022)
This study tries to find out how big the relationship between the influence of organizational culture variable and strategy business variable other performance organization variables, out by selected organizations in Indonesia, especially in the Jakarta area which is the largest tourism industry area in ASEAN. This research is motivated by various opinions regarding organization culture and strategy business can be performance organization for the tourism industry in Indonesia. the object, especially at the point of implementation which is still fully implemented even though organizational culture and strategy business are the necessary to comply with regulations and efforts to increase productivity and becomes and interesting thing in the background of this research. The organizational variable is focused on discipline innovation and clear division of authority, then the strategy business variable is focused on vision & mission strategy & tactics and marketing, and the performance organization is focused on the growth, customer satisfaction, and marketing. The number of samples obtained as many as 384 respondents from selected companies and the results of the research are as follows organizational culture and strategy business influences efforts to build performance organization, organizational culture influences performance organization, and strategy business influences performance organization